1988
DOI: 10.1080/02681102.1988.9627126
|View full text |Cite
|
Sign up to set email alerts
|

Information systems as social systems: Implications for developing countries

Abstract: Computer-based information systems should be conceptualised as social systems in which technology is only one of the dimensions. This broader perspective on information systems offers opportunities for a deeper understanding of their development and use. The social systems approach is illustrated in the paper by two research projects in the UK on the evaluation of information systems and information systems strategy formulation. The relevance of the UK research to a developing country context is discussed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 7 publications
0
48
0
1
Order By: Relevance
“…The challenges are linked to the lack of awareness of computers (among users and managers), lack of well trained IT professionals (who can bridge the gap between management and technology), inappropriate or weak infrastructure, lack of IT policies and strategic plans, and a weak culture of using computer based information (Bhatnagar, 1992;Sahay, 2001;Walsham, Symons, & Waema, 1988) in the context of LDEs.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges are linked to the lack of awareness of computers (among users and managers), lack of well trained IT professionals (who can bridge the gap between management and technology), inappropriate or weak infrastructure, lack of IT policies and strategic plans, and a weak culture of using computer based information (Bhatnagar, 1992;Sahay, 2001;Walsham, Symons, & Waema, 1988) in the context of LDEs.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural issues are a strong influence on any organisational change related initiative (Avgerou, 1993;Walsham, 1988) and e-government efforts in Zambia was no exception.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Most of these studies have focused on conditions rather than actions and behaviors, and on weaknesses rather than on ways of overcoming them (Montealegre, 1999). Furthermore, these studies pay little attention to how the interaction between IT and the organizations evolve over time (King, et al, 1992;Montealegre, 1997Montealegre, , 1998Walsham, et al, 1988). Most of the studies identified the problems or weaknesses of the contextual factors of IT, such as state of knowledge, availability of suitable equipment and infrastructure, lack of funding, and shortages of skilled personnel.…”
Section: The Need For More Researchmentioning
confidence: 99%